1988
DOI: 10.1136/gut.29.2.167
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of the lower oesophageal sphincter in the preterm baby.

Abstract: SUMMARY There are few reported studies of the lower oesophageal sphincter in preterm infants and none has investigated babies of less than 34 weeks gestation. Using a modified manometric technique suitable for use on very low birth weight infants we have measured sphincter pressures on 68 occasions in 25 infants of postconceptional age between 27 and 41 weeks. In even the most preterm infants the lower oesophageal sphincter could be defined. The mean effective sphincter pressure rose from 3-8 mmHg in infants o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(26 citation statements)
references
References 16 publications
0
24
1
1
Order By: Relevance
“…The elevation in pressure occurs progressively up to the 6th or 7th week of extrauterine life when, regardless of GA or BW, a sphincter high-pressure zone builds up, which has a higher capacity to avert reflux episodes. 30 The antenatal use of corticosteroids predisposes to GERD in preterm infants; 31,32 nevertheless, the results of the present study do not ratify this finding, possibly due to the small sample size used. Moreover, xanthines are a risk factor for GERD, as they change LES tone and increase the gastric production of hydrochloric acid, 4 but they were not statistically significant in this study, supposedly because the sample included very immature infants with a high frequency of xanthine use (89%), characteristics that are associated with BPD.…”
Section: Discussioncontrasting
confidence: 56%
“…The elevation in pressure occurs progressively up to the 6th or 7th week of extrauterine life when, regardless of GA or BW, a sphincter high-pressure zone builds up, which has a higher capacity to avert reflux episodes. 30 The antenatal use of corticosteroids predisposes to GERD in preterm infants; 31,32 nevertheless, the results of the present study do not ratify this finding, possibly due to the small sample size used. Moreover, xanthines are a risk factor for GERD, as they change LES tone and increase the gastric production of hydrochloric acid, 4 but they were not statistically significant in this study, supposedly because the sample included very immature infants with a high frequency of xanthine use (89%), characteristics that are associated with BPD.…”
Section: Discussioncontrasting
confidence: 56%
“…8,10,12 Esophageal pressure matures with increasing postconceptual age, leaving the infant at risk of reflux. 13 Gastric emptying is affected not only by gestational age, with transit through the gut observed at approximately 30 weeks, but also by the type of nutritional substrate present in the gut. 11 Human milk has been shown to facilitate gastric emptying, while feedings higher in energy density, fat, long-chain triglycerides, and dextrose delay gastric emptying.…”
Section: The Premature Gi System and Implications For Feeding And Nutmentioning
confidence: 99%
“…It is composed of specialized smooth muscle cells that manifest continuous electrical spike activity, causing tonic contraction. Newell and associates (6) (7) found that LES pressure rose from 3.8 mm Hg in preterm infants (Ͻ29 weeks' gestation) to 18.1 mm Hg in term infants. This has led to a generally accepted belief that the LES is incompetent in preterm infants.…”
Section: Physiology Of Ger In Preterm Infantsmentioning
confidence: 98%
“…It is estimated that about three to five GER events occur each hour in healthy infants. (4)(5) Using esophageal pH monitoring methodologies, Newell and associates (6) (7) found that episodes of acid GER are relatively common in asymptomatic healthy preterm infants, although the total time with acid in the esophagus was not abnormally high, indicating that refluxed gastric contents were cleared effectively from the esophagus. In another recent study using pH-metry, preterm infants had fewer episodes of acid GER when they attained full term postmenstrual age (PMA) than did healthy term-born controls.…”
Section: Epidemiology Of Ger In Preterm Infantsmentioning
confidence: 98%